Influence of Ultrafine Particles on Structure, Mechanical Properties, and Strengthening of Ductile Cast Iron; Metals; Vol. 8, iss. 7 - Zykova A. P. Anna Petrovna; Lychagin D. V. Dmitry Vasilievich; Chumaevsky A. V. Andrey Valerjevich; Popova N. A. Nataljya Anatoljevna; Kurzina I. A. Irina Aleksandrovna (2018, 2018)
Title screen